Contextual-Based Development of Early Children's Learning In the Era of the Industrial Revolution 4.0 - Nur Rahmah; Subhan Subhan; Nursyamsi Nursyamsi; Fitriani Fitriani; Nurliana Nurliana (Jurnal Syntax Transformation, 2024)
The world has now entered the era of industrial revolution 4.0, or the fourth industrial revolution, where information technology has become the main basis in human life. This research aims to: (1) describe early childhood Islamic learning in PAUD Palopo City; (2) describe contextual learning; (3) find a factual model of contextual-based learning; (4) find a contextual development model (draft) of early childhood Islamic learning. This research is a development research (R&D). The research was conducted in PAUD Parama Bunda, Libukang Permai, and Aisiyah Bustanul Athfal Palopo City. Informants in this study were education managers, principals, educators, and related parties who supported the research data. Data collection techniques used in-depth interviews, participatory observation, and documentation studies. Retrieval and checking the validity of data using triangulation techniques, reviewing key informants, and checking with members. Data analysis techniques used data reduction, data presentation, and conclusion drawing. Early childhood learning in Palopo City PAUD generally refers to service standards in organizing PAUD learning. Contextual-based learning planning is prepared in the form of curriculum, syllabus, semester program, weekly learning implementation plan (RPPM), daily learning implementation plan (RPPH). In practice, this learning is integrated with contextual learning. The contextual learning model is presented to the stakeholders involved for feedback and suggestions for improvement. The factual model was then revised and enriched in the form of a development model (draft) to make it easier to implement.